Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-56830-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency and Associated Risk Factors in Women from Riyadh, Saudi Arabia

Abstract: Vitamin D deficiency is an epidemic public health problem worldwide. It is common in the Middle East and is more severe in women. This cross-sectional study was conducted to assess vitamin D deficiency and associated risk factors in women living in Riyadh, Saudi Arabia. Serum 25-hydroxyvitamin D (25(OH)D) was measured in 166 women aged 30–65 years. Socio-demographic, lifestyle and health status characteristics, as well as intake of selected dietary supplements, were collected. Weight and height were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 37 publications
5
43
2
Order By: Relevance
“…However, it reported no association of VDD with age, educational, SES, employment, parity, body mass index, and sun exposure [ 30 ]. Another small cross-sectional study in Riyadh, Saudi Arabia, reported VDD among 60.2% of participants was associated with lack of usage of vitamin D, and multivitamins [ 31 ]. Another study in Riyadh, Saudi Arabia reported that absence of vitamin D supplements usage, younger age were factors associated with VDD among females [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it reported no association of VDD with age, educational, SES, employment, parity, body mass index, and sun exposure [ 30 ]. Another small cross-sectional study in Riyadh, Saudi Arabia, reported VDD among 60.2% of participants was associated with lack of usage of vitamin D, and multivitamins [ 31 ]. Another study in Riyadh, Saudi Arabia reported that absence of vitamin D supplements usage, younger age were factors associated with VDD among females [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than 60% of Middle Eastern people prefer burqa as appropriate dress for Saudi Arabian women [102]. On top of that, a study report showed that 60% of women from Saudi Arabia living in Riyadh city had vitamin D de ciency [103].…”
Section: Discussionmentioning
confidence: 99%
“…There was no association of VDD observed with age, educational, SES, employment, parity, body mass index, sun exposure (29). Another small cross-sectional study in Riyadh, Saudi Arabia, reported VDD among 60.2% of participants was associated with lack of usage of vitamin D, multi-vitamins (30).…”
Section: Resultsmentioning
confidence: 94%